Inclusive Culture in Compulsory Education Centers: Values, Participation and Teachers' Perceptions - Rosa-Eva; Ana María de Caso Fuertes; Roberto Baelo; Rosario Marcos-Santiago (MDPI AG, 2022)
This article explores teachers' perceptions concerning educational inclusion as part of an inclusive culture. The study focuses on compulsory education from the teachers' point of view. We used three factors indicated in the "Index of Inclusion": inclusive values, degree of participation in the educational community, and the teachers' perceptions of the educational response offered to SEN students. To comply with the proposed objective, we explored nine variables to understand their influence on the attitudes of teachers and other professionals towards educational inclusion. These variables were gender, age, teaching seniority, educational stage, professional profile, type of center, geographic location of the center, years of experience and characteristics of SEN students, as well as the training received to meet the needs of all students. We found significant differences in the variables of age, educational stage, student characteristics, and training received, and recommendations are provided to address the needs detected.